A literature review of recent advances in gastric cancer treatment: exploring the cross-talk between targeted therapies - Reza Panahizadeh; Padideh Panahi; Vahid Asghariazar; Shima Makaremi; Ghasem Noorkhajavi; Elham Safarzadeh (Cancer Cell International)
Abstract Background Gastric cancer (GC) ranks fourth in global mortality rates and fifth in prevalence, making it one of the most common cancers worldwide. Recent clinical studies have highlighted the potential of immunotherapies as a promising approach to treating GC. This study aims to shed light on the most impactful therapeutic strategies in the context of GC immunotherapy, highlighting both established and emerging approaches. Main body This review examines over 160 clinical studies conducted globally, focusing on the effectiveness of various immunotherapy modalities, including cancer vaccines, adoptive cell therapy, immune checkpoint inhibitors (ICIs), and monoclonal antibodies (mAbs). A comprehensive search of peer-reviewed literature was performed using databases such as Web of Science, PubMed, and Scopus. The selection criteria included peer-reviewed articles published primarily within the last 10 years, with a focus on studies that provided insights into targeted therapies and their mechanisms of action, clinical efficacy, and safety profiles. The findings indicate that these immunotherapy strategies can enhance treatment outcomes for GC, aligning with current treatment guidelines. ICIs like pembrolizumab and nivolumab have shown significant survival benefits in specific GC subgroups. Cancer vaccines and CAR-T cell therapies demonstrate potential, while mAbs targeting HER2 and VEGFR pathways enhance outcomes in combination regimens. We discuss the latest advancements and challenges in targeted therapy and immunotherapy for GC. Given the evolving nature of this field, this research emphasizes significant evidence-based therapies and those currently under evaluation rather than providing an exhaustive overview. Challenges include resistance mechanisms, immunosuppressive tumor environments, and inconsistent results from combination therapies. Biomarker-driven approaches and further research into emerging modalities like CAR-T cells and cancer vaccines are critical for optimizing treatments. Conclusions Immunotherapy is reshaping GC management by improving survival and quality of life. Ongoing research and clinical evaluations are crucial for refining personalized and effective therapies.